2014
DOI: 10.7314/apjcp.2014.15.20.8789
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Alpha Gene Expression in Breast Cancer Tissues from the Iranian Population - a Pilot Study

Abstract: Estrogen receptor alpha (ERα) is one of the major sub-types of estrogen receptors. ERα plays an important role in cellular proliferation and differentiation, chiefly in mammary tissues. In the present study we aimed to quantify of ERα mRNA and protein expression in breast tissues from the Iranian population using a real-time PCR assay. Twenty nine breast tissues including 19 adenocarcinomas and 10 normal controls were recruited from the Iranian population. mRNA extraction and cDNA synthesis were performed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…ERα has an important function in BC progression through cell growth and proliferation induction. It has been shown that there was an increased expression of ERα in the levels of mRNA and protein in a sub population of Iranian BC tissues in comparison with normal margins and it was associated with tumor size [234]. A mutational analysis has also shown that the presence of the ERα gene A908G mutation among a sub population of Iranian cases with invasive BC.…”
Section: Main Textmentioning
confidence: 99%
“…ERα has an important function in BC progression through cell growth and proliferation induction. It has been shown that there was an increased expression of ERα in the levels of mRNA and protein in a sub population of Iranian BC tissues in comparison with normal margins and it was associated with tumor size [234]. A mutational analysis has also shown that the presence of the ERα gene A908G mutation among a sub population of Iranian cases with invasive BC.…”
Section: Main Textmentioning
confidence: 99%